The extreme poverty in Bangladesh: an overview - Halder, Shantana R.; Husain, A.M.Muazzam (Research and Evaluation Division, Brac, 2019)
By reviewing existing literature this report focuses on methodological issues related to the identification of ultra poor in Bangladesh. According to different statistics up to 40% of the rural poor in Bangladesh remains uncovered by any micro-credit initiatives. Extreme poor consists of 30-40% of that population. Extreme poor are of two types. It includes destitutes and those who are physically fit for work but unable to consume more than 1805 kilo calories per person per day. The extent of extreme poverty and its actual number varies depending upon the methods used for calculation. Since there is no universally accepted definition on extreme poverty, it also creates another problem in its measurement. It is revealed from the findings of different studies that a single criterion is not enough to identify the extreme poor. In this regard a combination of variables highly correlated with poverty like household landholding, household head's sex, education and occupation and village level vibrancy can be a better choice.